2021
DOI: 10.3390/biomedicines9060693
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer: Biomarkers and Targeted Therapy

Abstract: Ovarian cancer is one of the most common causes of death in women as survival is highly dependent on the stage of the disease. Ovarian cancer is typically diagnosed in the late stage due to the fact that in the early phases is mostly asymptomatic. Genomic instability is one of the hallmarks of ovarian cancer. While ovarian cancer is stratified into different clinical subtypes, there still exists extensive genetic and progressive diversity within each subtype. Early detection of the disorder is one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 163 publications
(130 reference statements)
0
31
0
Order By: Relevance
“…Experiments in recent years have established that the growth, division, metastasis, and invasion of OC cells are controlled by eRNAs [ 23 , 24 ]. It is possible that the abnormal expression of some lncRNAs in OC will provide useful information for the diagnosis and treatment of patients, as well as their prognosis [ 25 , 26 ]. However, the investigation of eRNAs for OC is still in its infancy compared to miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in recent years have established that the growth, division, metastasis, and invasion of OC cells are controlled by eRNAs [ 23 , 24 ]. It is possible that the abnormal expression of some lncRNAs in OC will provide useful information for the diagnosis and treatment of patients, as well as their prognosis [ 25 , 26 ]. However, the investigation of eRNAs for OC is still in its infancy compared to miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection and cisplatin chemotherapy are the preferred choices for the treatment of ovarian cancer, but because early screening factors are not obvious, symptoms only appear in the late stage, and the 5-year survival rate can be as low as 30% 59 , 60 . At present, studies have found that HMGA1 can regulate the expression of stem-related genes in ovarian cancer, such as KLF4, SOX2 and ABCG2, a drug-resistant protein, increasing the resistance of ovarian cancer to paclitaxel 61 .…”
Section: The Role Of Hmga1 In Cancermentioning
confidence: 99%
“…The lack of methods for early detection of OC is a major obstacle, leading to a high rate of diagnoses with advanced-stage (III-IV) disease that hinders therapy efficiency [ 4 ]. The principal hallmark of advanced-stage OC is ascites—the accumulation of excessive fluid containing cellular and acellular components in the abdomen [ 5 ].…”
Section: Introductionmentioning
confidence: 99%